Development of a clinician–parent home care education intervention. (30th October 2019) - Lane, Blake; Hanke, Samuel P.; Giambra, Barbara; Madsen, Nicolas L.; Staveski, Sandra L.
Abstract: Objectives: To examine the strengths and opportunities for improvement of current home care education practices to inform the development of the Home Care for Heart Health intervention, and to develop a web-based intervention for parents and clinicians with complimentary print materials that could provide the right education at the right time to foster a safer transition from hospital to home. Methods: An inter-professional focus group of parents, clinicians, and designers was formed to co-create a home care education intervention for parents of children with congenital heart disease (CHD) and their care team. We used the Integrated New Product Development process model created by Jonathon Cagan and Craig Vogel at Carnegie Mellon University to develop the intervention. This process model is a way of thinking that combines horizontal and inter-disciplinary teams, stakeholder-centric focus, and a system of qualitative discovery and development evolving towards quantitative methods of refinement. Results: Our team developed the Home Care for Heart Health intervention. The evidenced-based intervention includes a quick reference guide for parents of children with CHD, an accompanying app, family-friendly pathways, and clinician education. Conclusion: Using an inter-professional approach, our team of clinicians, parents, and design experts were able to co-create a clinician–parent home care education intervention with broad application and lifelong relevance to the Congenital Heart Disease Community. Practice Implications: Our intervention has the potential to be used as a model for other home care education interventions for parents of children with chronic illnesses.